EXPLORING THE ROLE OF PRAGMATICS IN CROSS-CULTURAL COMMUNICATION - Abdullaeva Gulkhayo Ulugbekovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
In today's globalized world, effective communication across cultures has become more significant than ever. This paper investigates features of pragmatics, a branch of sociolinguistics that explores how context shapes the meaning of language, in particular, in cross-cultural communications. Besides, this article explores how cultural norms and values impact pragmatic conventions, starting with an overview of pragmatics and its key concepts. Through analysis of cultural differences in politeness strategies, indirectness, and speech rituals, it becomes obvious that misunderstandings frequently occur in intercultural communication because of differing pragmatic norms. Nevertheless, some approaches are also offered to navigate these challenges, emphasizing the significance of awareness and sensitivity to pragmatic differences. Readers gain insight into the practical applications of understanding pragmatics in diverse contexts. Finally, future directions for research in cross-cultural pragmatics are also highlighted.